2021
DOI: 10.1158/1535-7163.mct-21-0071
|View full text |Cite
|
Sign up to set email alerts
|

Gilteritinib Inhibits Glutamine Uptake and Utilization in FLT3-ITD–Positive AML

Abstract: Acute myeloid leukemia (AML) with a FLT3 internal tandem duplication (FLT3-ITD) mutation is an aggressive hematologic malignancy associated with frequent relapse and poor overall survival.The tyrosine kinase inhibitor gilteritinib is approved for the treatment of relapse/refractory AML with FLT3 mutations, yet its mechanism of action is not completely understood. Here, we sought to identify additional therapeutic targets that can be exploited to enhance gilteritinib's antileukemic effect. Based on unbiased tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…In this study, we have similarly found that FLT3 inhibition enhances AZD5991-induced cytochrome c release. Given that gilteritinib treatment has been reported to decrease the oxygen consumption rate in FLT3 -ITD AML cells, indicating a reduction in oxidative phosphorylation [ 44 ], this may also play a role in the mechanism of action, though further investigation into this mechanism of action is beyond the scope of this manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have similarly found that FLT3 inhibition enhances AZD5991-induced cytochrome c release. Given that gilteritinib treatment has been reported to decrease the oxygen consumption rate in FLT3 -ITD AML cells, indicating a reduction in oxidative phosphorylation [ 44 ], this may also play a role in the mechanism of action, though further investigation into this mechanism of action is beyond the scope of this manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…For example, glutaminolysis was identified as synthetically lethal with FLT3-TKI treatment, indicating the potency of using amino acid depletion in combination therapies [ 56 , 57 ]. Another FLT3-TKI gilteritinib was also proved to hinder glutamine uptake and utilization in FLT3 -ITD–positive AML [ 58 ]. Recently, NEI-01, a novel arginine-depleting enzyme, could not only induce arginine deprivation, but also had cytotoxic activity against arginine auxotrophic AML cells through induction of cell cycle arrest and apoptosis [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In FLT3-internal tandem duplication (FLT3-ITD)-positive AML, a subtype of leukemia with notoriously dismal outcome, CB-839 also impaired GSH production, induced severe mitochondrial oxidative stress and cell apoptosis. More remarkably, CB-839 and FLT3 inhibitors, including AC220 and gilteritinib, exerted synergistic pro-apoptotic effects and displayed more potent anti-leukemia effect (42,43). These redox-targeted combinations represented a novel therapeutic strategy with high efficiency, low toxicity and enormous potential for clinical translation (44).…”
Section: Glutaminementioning
confidence: 99%